Dynamic capabilities in strategic choice processes within organisations = Dynamiczne zdolności w procesach strategicznych wyborów organizacji - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
Dynamic capabilities are an essential theoretical construct that is useful for understanding the phenomenon of competition. Still, in spite of the apparent popularity of this subject, the existing management literature could do with more studies into processes that shape dynamic capabilities.
Keywords: Zarządzanie strategiczne; zdolności dynamiczne; zdolności operacyjne; konkurencyjność; organizacje współczesne; dynamic capabilities; operational copabilities